Through the looking glass: what do we see, what have we learned, what can we share? Information management at the Shortgrass Steppe Long Term Ecological Research site - Zeimet, Adam, author; Beer, Dianne, author; Norman, John, author; Bennett, Christopher W., author; Flynn, Bob, author; Stafford, Susan G., author; Kaplan, Nicole E., author; SGS-LTER, Colorado State University, publisher (Colorado State University. Libraries, 2009)
This poster displays the development of a successful information management system at a Long Term Ecological Research (LTER) site that has a rich history of data collection and management. Over sixty years of data from three separate projects are incorporated into the Shortgrass Steppe (SGS) LTER information management system and databases. People with different strengths and expertise ranging from clerical administrator, programmer, to ecologist, have filled the role of Information Manager (IM) at the SGS-LTER. Today the information management needs of the SGS are provided by a team of IMs with various levels of expertise in a wide variety of domains from information technology administration to education and outreach. It is critical for IMs at any long-term research site to understand how information and data were managed in the past and what recent changes have been added to the system, in order to effectively implement a management plan for the future. We are able to evaluate the effectiveness of different approaches to information management and have a commitment to share our successes with the information management community.
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Colorado State University. Natural Resource Ecology Laboratory; Colorado State University. Department of Forest and Rangeland Stewardship; Colorado State University. Department of Soil and Crop Sciences; Colorado State University. Department of Biology; California State University, Fullerton; United States. Agricultural Research Service; University of Northern Colorado.
Keywords: long term ecological research; shortgrass steppe; grassland ecology; Pawnee National Grassland; Central Plains Experimental Range